University Students’ Perception of the Use of Artificial Intelligence in their Education (Docentes 2.0 Journal, 2025)
Artificial intelligence (AI) has established itself as one of the most transformative disciplines in recent decades, redefining key sectors of society, including education. This research aimed to explore the perceptions and feelings of students at the Technological University of Nezahualcóyotl (UTN) regarding the use of AI tools in their learning. The research was conducted within the positivist paradigm, employing the hypothetical-deductive method, a quantitative approach, and a non-experimental, descriptive, cross-sectional design. A Likert-scale instrument with closed-ended questions was administered to 2,282 students aged 17 to 30 years from different areas of knowledge at the university. The results revealed that regardless of whether students use AI, 3.86% of the population showed negative attitudes, compared to 61.26% with positive perceptions (p = 0.0002). The Division of Basic Sciences and Engineering had the lowest representation in positive feelings (p = 0.002). The perception of positive feelings by gender showed no significant differences; however, the age group most accepting of AI is 26-30 years. On the other hand, 34.88% of the population showed neutral feelings. These findings suggest the need to train students in the ethical and critical use of AI across various areas of study. This approach promotes its responsible integration as an everyday tool, enabling them to leverage technologies to address future professional challenges and consolidate its potential as a transformative educational resource.
Keywords: Artificial Intelligence; Digital Datives; feelings; University Students